CODESRIA Bulletin Online, No. 7, March 2021: Ghana’s Democracy and the 2020 General Election: Signs of a Fading Promise? - Lloyd G. Adu Amoah (CODESRIA Bulletin, 2021)
Introduction Ghana’s 2020 general election was unique because, for the first time ever, the presidential election involved a former President who had just lost power. Fresh from a thumping defeat in 2016, John Dramani Mahama stood again on the National Democratic Congress (NDC) presidential ticket.1 Nana Addo Dankwa Akufo-Addo of the New Patriotic Party (NPP) had beaten him for the presidency by an impressive 984,570 votes – five times the total number of votes cast for the other five candidates. For some close watchers of Ghana’s burgeoning democracy, the reemergence of Mahama was a convincing sign of Ghana’s sterling democratic credentials because the 1992 Constitution was defining the rules of the political game (Lenhardt et al. 2015). In that sense, then, the 2020 election was part of the fairy tale run of Ghana’s relative electoral good fortune that had seen three successive successful peaceful changes of power between the two dominant parties. While there had been no cudgels, loss of life, or loss of property in these changes of power between the NDC and the NPP, any euphoria expressed over the health of Ghana’s democracy may have been premature. The Policy Pathology: Democracy without Development The political processes that led to the 1992 Constitution being adopted and coming into force on 7 January 1993 had an unmistakably material rationale (Ninsin 1998). Given that Ghana had been through a long period of political and economic turmoil after 1966, this rationale makes sense. The 1992 Constitution was expected to provide the legal, moral and political base for a system of liberal democratic governance that would bring long-awaited prosperity to Ghana. Jerry Rawlings’ campaign for the presidency in 1992 had emphasised just that – stability and consolidation. In other words, Rawlings was telling Ghanaians that voting for him meant that constitutional rule would further deepen the putative stability his military rule had wrought and promote even more economic gains. It thus can be argued that the 2016 general election was an unofficial referendum on the fruits of Ghana’s democracy in its twenty-third year. As Figure 1 shows, Ghana’s economic performance in the second decade of the twenty-first century was mixed.2 Indeed, over the period 2000–2020, the country’s economy has not been able to record the consistent double digit growth rates seen in certain Asian Tiger economies and touted by neoclassical economics as the necessary basis for economic transformation and development. This state of affairs rankles because the John Atta Mills and Mahama administrations ran an economy in which oil had become a key part of Ghana’s exports; a valuable commodity that was expected to deliver prosperity (Fosu 2017). The lack of prosperity was a central pillar of 2016 general election campaigns. It is not surprising therefore that the NPP ran a campaign in which Mahama was described as an incompetent leader presiding over a corrupt administration and thus incapable of delivering the economic and social nirvana that Ghana so desperately deserved and desired. This toxic combination of corruption and incompetence (Pulse 2016) was not just in local view. At the 2014 World Cup football tournament in Brazil, in full view of the world, the Ghana Football Association delivered US3million in cash to the national football team, the Black Stars (BBC Sport 2014). If the 2016 election is seen as a kind of referendum, the question was whether Mahama or AkufoAddo could deliver the longawaited fruits of democracy. The election results showed that the overwhelming majority of Ghanaians considered Akufo-Addo to be the competent and incorruptible candidate for the task at hand (see Emmanuel 2015). Figure 1: Ghana’s Economic Performance in the first two decades of the 21st century. Source: Amoah (2020) (Voir PDF) The 2020 Election and the Persistence of the Policy Pathology Akufo-Addo’s resounding victory in the 2016 polls meant he had been given one of the firmest mandates ever in the country’s contemporary political history and set this West African nation on a firm and robust path to answering what Ghanaian academic Ninsin (2019) has described as the “welfare” question.3 However, by the time the 2020 elections were held, the voters’ view of which candidate was corrupt and incompetent had switched. The failure of the Akufo-Addo team to properly credit a section of his inaugural speech set tongues wagging about incompetence, something that seemed to hang about for the entire four years he was President, despite his undertaking that the NPP had the men and the women that would give Ghanaians a decent standard of living (Akufo-Addo 2015). His administration was also accused of corruption. Two scandals stand out – the Power Distribution Service (PDS) scandal (Mallory 2019), and the Agyapa Gold Royalties scandal (Amin 2020). Claims were made in both cases that prominent Ghanaians with family and friendship ties to Akufo-Addo had tried to use these connections to unfairly gain control of the strategic sectors of power and minerals at the expense of the larger interests of Ghana. Akufo-Addo fought back during his 2020 campaign by touting some of his government’s flagship policy changes, particularly the Free Senior High School policy.4 By July 2020, GH¢3.2 billion (over US5billion) had been spent on implementation on the SHS, the largest investment in a new policy introduced by the NPP government. The NDC under Mahama ran a campaign dubbed “The Rescue Mission”. The 2020 NDC campaign manifesto sought to position the party as more welfare-orientated than the NPP, underscoring how important material security imperatives had become for Ghana’s elections. The NDC responded to the NPP’s education policy boast by raising the education stakes. It promised that, if it became the next administration, 50 per cent of tertiary-level study fees would be absorbed by government. The 2020 election results vividly showed the waning patience of Ghanaian voters towards both parties. The NPP lost its 63-seat majority in the Ghanaian Parliament and the party was left with only one seat more than the NDC. This created the Fourth Republic’s first hung parliament. Akufo-Addo received 467,165 fewer votes than in 2016, bringing his winning margin down to 517,405 votes. While there was no doubt that Ghanaian voters chose the NPP candidate, it did not give the party its muchneeded control of the legislature. Tackling the Sources of the Policy Pathology It is not difficult to work out why Ghana’s democratic promise is failing to materialise, especially with respect to meeting the legion welfare needs of the country’s people. The pervasive party system that has come to control every facet of Ghanaian life easily comes up for critique. Kwame Ninsin has drawn attention to what I describe as the ‘party system perversion’ encapsulated in Ghana’s NPP-NDC party duopoly: since the 1992 Constitution came into force, the electoral system of winner-takes-all has provided a powerful impetus for one of the two major political parties – the National Democratic Congress (NDC) and the New Patriotic Party (NPP) to control state power, entrench themselves in the architecture of governance of the country, and appropriate associated material resources to enhance their economic and social status (Ninsin 2018: 61). To draw an analogy from anatomy, the party is the heart which, working through capillaries, veins and arteries (membership and structures from the regional to the unit level), seeks to realise the material, political, social and psychological interests of its members even to the detriment of the Ghanaian state. Almost reminiscent of the Nkrumah era, Ghana’s two dominant parties become supreme once in power; a supremacy that the 1992 Constitution has counterintuitively made possible. Ninsin (2018: 61) puts it well: ‘once in power the victorious political party exercises the panoply of executive and legislative powers available under the constitution to control the full range of existing economic, political and social institutions’. Winning power by any means necessary, fair or foul, seems to have become the raison d’etre for Ghana’s dominant parties for, in seizing the political kingdom, all things are added onto the party. As a consequence, these parties have become election-winning machines that are pump-primed every four years to win power using a mind-boggling amount of human and financial resources beyond what the Ghanaian state has at its disposal. In other words, winning power has become an instrument for party members to achieve their material and other goals. The party membership card is the ticket for one’s well-being. It seems that merely bearing Ghanaian citizenship is not enough. Ironically, it is the current democratic order that has made all this possible. The upshot of all this is a morbid partisanship which makes enemies of members of opposing political parties and non-party card-bearing citizens alike. This partisanship trumps the patriotism which has become too costly to reveal, let alone actively practice. What all of this has done is to spawn an insidious socio-political atmosphere of deep mistrust, thick insularity, and manic self-seeking in which gathering the best talents and minds for national reconstruction has become a secondary consideration if contemplated at all. This state of affairs was on display quite graphically on the dawn of 7 January 2021 when members of the newly elected 8th Ghanaian Parliament could not agree on which group should sit on the right of the Speaker and which on the left. It must be added here that, in 2012 and again in 2020, the Supreme Court of Ghana has been called upon to resolve election disputes.5 In both cases, the parties who petitioned the courts (the NPP in 2012 and the NDC in 2020) found fault with the Electoral Commission of Ghana; a curious case of parties mistrusting the Commission only when they lose. What this hints at is whether key national institutions are autonomous and free from the manipulation and control of those who wield political power. As the 2024 election approaches, the issues discussed in this paper and the ways they impinge on the viability of Ghana’s democratic journey, especially in respect of its material deliverables, cannot be wished away. Many fundamental questions need to be answered. Can Ghana’s dominant parties move away from their obsession with winning power and become vehicles for responding to Ghana’s existential problems? Will merit become the foremost consideration for appointment to the highest strategic positions of state instead of party membership and loyalty? Will the perception that party members can get away with lawlessness be demonstrably dealt with? These are some of the pressing questions that need to be addressed if Ghana’s democracy is to live up to its normative and material promise. Time will tell. Notes This was the first time an incumbent president seeking a second term in the Fourth Republic had been defeated, and this happened in the first round of voting. For more on the continuities and departures of contemporary Ghanaian elections see the insightful analysis by Frempong (2019). In this decade Ghanaian democracy could be arguably described as fairly consolidated. In 2016 the 7th Parliament was in place under the Fourth Republic and the presidency had been occupied by five people. See also Ninsin Through this policy, the Government of Ghana took up the issue of fees for senior secondary education, something that had not been tackled prior to 2016. At the time of writing, the Supreme Court of Ghana had set 4th March, 2021 as the date for it to hand down its judgment on the petition challenging the election of Akufo-Addo in the 2020